Understanding 'fairness' in student selection: are there differences and does it make a difference anyway? - Pitman, Tim (Routledge, 2014)
Universities are required to adopt 'fair' student admission practices, yet understandings of fairness in student selection are contested. This paper uses an analysis of the admission policies of Australia's public universities to critically examine the use and application of notions of fairness. A further analysis of enrolment data is used to contextualise policy rhetoric against admission practice. Three broad themes of fairness emerge: merit based, procedural and normative. Discursively, merit-based fairness is the preferred understanding of fairness. The enrolment data, however, indicate no relationship between how fairness is explicated and whether or not a university is more accessible to disadvantaged students. In practice, therefore, normative conceptualisations of fairness are the most influential, when normative fairness is understood as a reproduction of wider social inequities.